Key problems of the quality of life of patients after total laryngectomy - Slouka, David; Kučera, Radek; Hošek, Petr; Gál, Břetislav; Trčka, Ondřej; Kostlivý, Tomáš; Havel, David (Kontakt, 2018)
Introduction: Laryngeal cancer is the most frequent cancer in the head and neck area. Approximately one third of patients are treated by total laryngectomy (TL). The rate of the patient's adaptation to new conditions is crucial to the quality of his or her future life. Some patients survive tens of years after this operation. The preparation for TL is a complicated process that affects a patient's cooperation in postsurgical time. The patient is informed of the essence of the disease, treatment possibilities, the process of preoperative preparation, as well as the operation itself. Great emphasis is put on awareness of the postoperative development, the patient's good cooperation, as well as good prognosis of the disease. Losing one's voice and the cosmetic defects caused by the tracheostoma are a great problem for the patient. The aim of this study was to show the main problems that patients after total laryngectomy deal with in common life. Material: In the group, there were 102 patients who had been operated on between 2003 and 2013, 62 of which met the classification criteria. Methods: This prospective study was statistically evaluated. The frequencies of responses were processed in tables. Results: During the early postoperative period, the greatest problem of patients after total laryngectomy is their adaptation to new principles of breathing, which is subsequently followed by the adaptation to a new and different way of communication. The best option for the patient is to communicate using esophageal voice. Only 55% of operated patients use one of the verbal forms of alternative voice communication in their future lives.
Keywords: Laryngeal Neoplasms; Laryngectomy; laryngektomie; komunikace; sociální přizpůsobení; Prospective Studies; nádory hrtanu; Voice Disorders; Communication; Quality of Life; Social Adjustment; prospektivní studie; kvalita života; poruchy hlasu